MENINGKATKAN HASIL BELAJAR SISWA DENGAN METODE TANYA JAWAB DI MTSN LANGSA - Lismawati (At- Tarbawi, 2019)
The purpose of this study was to determine student learning outcomes after being taught with the question and answer method. The approach used in this study is a qualitative approach and the type of research is classroom action research consisting of 2 cycles. Data analysis uses comparative descriptive analysis techniques by comparing initial conditions with the results achieved in each cycle and qualitative descriptive analysis of observations and reflections in the first cycle and second cycle. The subjects in this study were students of class VIII-1 MTs Negeri Langsa with a total of 36 students in the class. Based on this study it can be concluded that there is an increase in the ability of students to master the material of the human circulatory system by using the question and answer method in the State of Langsa State in 2015/2016. Improved student learning outcomes can be seen in the tabulation of the data obtained, namely the first cycle of 10 students (27.78%) who completed and 26 students (72.22%) did not complete. Then in Cycle II there were 35 students (97.2%) complete and 1 student (2.8%). incomplete. On this occasion the researcher wanted to give some suggestions to be conveyed as follows: The need to use methods when providing subject matter so that students are easy and the learning process becomes fun.